KERJASAMA PERDAGANGAN ANTARA INDONESIA DENGAN SPANYOL DALAM BIDANG KELAUTAN SEKTOR PERIKANAN PADA KERANGKA KERJA PCA (PARTNERSHIP COOPERATION AGREEMENT) TAHUN 2014-2017 - Fenny Desty; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research analyzed the Trade Cooperation in the fishery sector Indonesian fish exports to the European Union especially Spain. In this case Indonesian experienced an increase in the production of fishery commodities while then Spain fishery industry was unable to meet its own domestic needs, so it hard to import from other countries one of which was Indonesian. This Trade Cooperation supported by the Partnership Cooperation Agreement (PCA) between Indonesian and the European Union with Spain as one of its members. In one of it’s srticless stated the commitment of the two parties to carry out Cooperation include Trade Cooperation and Illegal Fishing Eradication. European Union commitment is proven by giving sanction to some fish importing countries to the European Union because illegal fishing issuise.The method used in this research is a qualitative research, with library research method. Some of the data obtained come from books, journal, articles, internet and other media. In this study also use the perspective of liberalism. The theory used is the theory of International Economic Cooperation found by Caraiani and Georgeus and the use of the level analysis namely the Nation-State. Government of Indonesia and Spain come as Internasional actor.The PCA agreement greatly help Indonesia in Importing fishery products to Spain as evidenced by the increase in export volume in the January-April 2016 period. Indonesia’s fishery product export to Spain reached US 8.059.786 increasing by 221,3% when compared to the export value of the same period in 2015 which reached US 2.508.467.Keyword : Indonesia-Spain, Partnership Cooperation Agreement (PCA), Illegal Fishing